Pengaruh Kompensasi Dan Lingkungan Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Mediasi pada Super Dazzle Geyajan - Rakha Samboga; Muhammad Subkhan (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The purpose of this study is to examine how Super Dazzle Gejayan's pay and work environment affect staff performance, using job satisfaction as a mediating variable. Quantitative research is the research methodology employed. The 142 employees of Super Dazzle Gejayan made up the study's population. Partial Least Square (PLS) with Convergent Validity, Factor Loading, Cronbach Alpha Discriminant Validity, Cross Loading, Reliability, Composite Reliability, R Square, and Hypothesis Testing tests were used to analyse the study's sample of 60 respondents. According to the study's findings, pay has no bearing on worker performance, while work environment has a positive and significant impact on worker performance. Job satisfaction also has a positive and significant impact on worker performance, and compensation has a positive and significant impact on worker satisfaction. Job satisfaction also acts as a mediating variable in the relationship between work environment and worker performance.